Incidences of Minor Sexual Abuse in Sahibzada Ajit Singh (SAS) Nagar District, India: A Retrospective Study of 5 Years - Natasha Thakur (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: The incidences of child sexual abuse are increasing nowadays due to lack of awareness, child neglect,misuse of social sites, family violence, and much more. The present study aims to determine the socio-demographicprofile of past five-year cases of child sexual abuse of SAS Nagar district.Materials and Methods: The study was conducted on 114 cases of child sexual abuse registered under the POCSOAct, 2012. The period chosen was from 1st January 2013 to 31st December 2017, located in the SAS Nagar District,Punjab. The data was collected through RTI from the SSP office of SAS Nagar. The details were pertaining tosocio-demographic parameters (age, sex, marital status, occupation, and profession), relationship with accused,place of incidence, the time interval between the date of incidence and date of reporting case noted in a selfdesignedPerforma.Results: There were a maximum number of child sexual abuse cases in 2017, 34 followed by 33 cases in 2015. Thecases of female sexual assaults (92.98%) outnumbered male sexual assaults (2.76%). The commonplace offense wasthe accuser’s house (22.80%). The most vulnerable age group was 11-15 years (46.49%). 51.75% of the alleged sexualassault victims were students. Unmarried victims were 97.36%. Most commonly, sexual crimes were committedby the person known to the victim (89.48%). Maximum numbers of cases were reported on the 2nd day of incidence(35.08%).Conclusion: Developing moral values and ethics among people in the transitional phase of cultural devaluationand organizing minor sexual assault prevention programs in ways that contribute to the community’s owncapacity to prevent this heinous crime is crucial as the biggest threat to the minors is not from the strangers butfrom the known and close ones.